COPING BEHAVIOR OF PRIMARY SCHOOL СHILDREN IN VARIOUS DIFFICULT LIFE SITUATIONS - ROKSANA M. BAYRAMYAN; KIRILL S. CHULYUKIN (Консультативная психология и психотерапия, 2022)
Relevance. The article is an analysis of theoretical and empirical modern research in the field of coping behavior with difficult life situations (DLS) and psychological well-being of primary school children. It is stated that copings in primary school age have a pronounced age specificity. Objective. The sources of DLS and coping strategies of younger schoolchildren are systematized. Methods. Theoretical analysis of domestic and foreign studies of coping behavior with DLS in primary school age. Results. Two groups of the DLS genesis are identified in which the coping behavior of children is actualized — the first one is related to the environment (academic, natural, etc.), the second is related to interpersonal interactions (relationships with teachers, peers, etc.). Depending on the group, the corresponding coping strategies are identified. The conclusion is made firstly about the risk groups for non-coping with stress in primary school age and secondly about the need to form effective strategies that are insufficiently formed.